Gas exchange, root hydraulic conductivity, water use efficiency and the growth of Toona ciliata clones and seedlings - Freitas de Oliveira, Taiane Pires de; Barroso, Deborah Guerra; Moura de Assis Figueiredo, Fabio Afonso Mazzei; Barros, Thais Chagas [UNESP]; Gambetta, Gregory A.; Campostrini, Eliemar (Centro Pesquisas Florestais, Ufsm, 2019)
Forest plantations established with seedlings have heterogeneity and are difficult to manage, so an alternative is the use of clones with high productivity. In addition, clonal plants differ in the structure of the root system that can influence the water and nutrient uptake efficiency and therefore productivity. We evaluated leaf gas exchange, root hydraulic conductivity, and water use efficiency of Toona ciliata clonal cuttings and the seedlings growth. The study was performed in a completely randomized design with four treatments: a) TC3 clone; b) TC9 clone; c) TC15 clone and d) seedlings with five replicates and ten plants per plot. On the 120th day, the net photosynthetic rate, transpiration and stomatal conductance were evaluated between 12:00 and 13:00 hours and the values calculated as efficient, instantaneous (A/E) and intrinsic (A/gs) water use were calculated. Hydraulic root conductivity (k(root)) was obtained by applying increasing pressures (0.1, 0.2, 0.3, and 0.4 MPa) using Scholander chamber. The height, stem diameter, leaf area, dry mass of shoot and root, length, diameter, surface area and root volume were also determined. The data were submitted to Pearson's correlation and analysis of variance, comparing by Tukcy's test (5%). The genetic materials studied presented an equal capacity of water absorption and transport by the roots, even though they exhibited a visual anatomical differences of the root system. Although, the clones exhibited low transpiration and net photosynthetic rates, they were generally more efficient in water use, and the TC3 and TC9 clones were more efficient to convert the assimilated carbon to biomass.
Keywords: Photosynthesis; Root hydraulic conductivity; Toona ciliata; Cuttings